Adjustment Of Income Tax for Employee Based On Average Effective Rate (TER) Scheme. Is This Effective? - Achdian Anggreny Bangsawan; Hasnidar Syam; Nuraini Amiruddin (IECON: International Economics and Business Conference, 2024)
This study aims to analyze the differences between calculating PPh 21 for employees using the TER scheme and previous provisions and how the impacts both the company and employee. This research was conducted using a qualitative descriptive approach. Data collection techniques through literature studies and interviews. Data analysis techniques using comparatives analysis. The process of calculating monthly PPh 21 is indeed simplified by using the TER scheme, but the risk of overpayment or underpayment at the end of the year can add to the complexity of tax management for companies and employees. This policy only shifts the complexity of calculating PPh 21 to the end of year. Research result show that the process of calculating monthly PPh 21 is indeed simplified by using the TER scheme, but the risk of overpayment or underpayment at the end of the year can add to the complexity of tax management for companies and employees. This policy only shifts the complexity of calculating PPh 21 to the end of year. Although this policy has a good intentions, its impact on companies and employees is still debatable, especially in terms of the fairness and effectiveness of simplication. For companies, managing tax underpayments and overpayments at the end of year can add to the administrative burden and affect cash flow. This policy also effects the amount of take home pay employees receive each month.